Electoral Advertising in the Digital Era: Legal Limits and Regulatory Challenges - Martins, Rayka Camilo; Pidde, Giovana Alves Ribeiro Tavares; Pereira, Lara Luiza Silva; Silva, Érica Freire da; Oliveira, Lucas Gabriel Mendes de; Silva, Letícia Freire da; Gonçalves, Amanda Costa; Castro, Ayeska Lavinea de Oliveira (CIPEEX, 2025)
Due to technological advancement, the dissemination of information has become increasingly accessible, reaching different parts of the world and directly impacting democratic processes, particularly given the growing incidence of Fake News. The objective of this study was to examine the mechanisms of electoral advertising in the Digital Era, emphasizing its challenges and legal constraints within the new reality of online communication. The methodology adopted consisted of legislative analysis and bibliographical research. The use of the internet in electoral campaigns was first regulated by Brazilian Federal Law No. 12,034, of September 29, 2009, which established specific provisions for digital electoral advertising. This legislation authorized websites, blogs, and social media in campaigns, provided compliance with the established rules. Social and technological transformations generate new demands in the electoral sphere, requiring the legal framework to adapt to emerging needs. A bibliographical study was conducted based on academic articles, legislation, and publications of electoral courts, employing a qualitative methodology and highlighting changes since the advent of digital media, particularly in recent Brazilian electoral scenarios. Findings demonstrate that the dissemination of Fake News for electoral purposes may compromise equality among candidates, undermine judicial oversight, and foster hostility in campaigns, potentially amounting to abuse of power depending on circumstances and actors involved. It is concluded that electoral advertising on digital platforms must be carried out with caution and responsibility, as the improper use of such tools, especially through misinformation, tends to impair process integrity, intensify conflicts between candidates, and destabilize competition. Ensuring regulation and accountability is essential to safeguarding democracy in the Digital Era.